2022
DOI: 10.1088/1361-6560/ac6b10
|View full text |Cite
|
Sign up to set email alerts
|

Implicit neural representation for radiation therapy dose distribution

Abstract: Objective. Dose distribution data plays a pivotal role in radiotherapy treatment planning. The data is typically represented using voxel grids, and its size ranges from 10^6--10^8. A concise representation of the treatment plan is of great value in facilitating treatment planning and downstream applications. This work aims to develop an implicit neural representation of 3D dose distribution data. Approach. Instead of storing the dose values at each voxel, in the proposed approach, the weights of a multilayer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1
1

Relationship

4
2

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 14 publications
0
10
0
Order By: Relevance
“…iDoTA is trained using a certain resolution and grid dimensions, which must be fixed for both training and inference. For dose prediction in finer grid resolutions, iDoTA can be coupled to neural representation models capable of accurate super‐resolution 50 . Regarding grid size, predicting dose distributions from treatment plans or beams through anatomies larger than the predetermined voxel grid must be done in steps, obtaining several input volumes and accumulating the outputs along the beam depth.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…iDoTA is trained using a certain resolution and grid dimensions, which must be fixed for both training and inference. For dose prediction in finer grid resolutions, iDoTA can be coupled to neural representation models capable of accurate super‐resolution 50 . Regarding grid size, predicting dose distributions from treatment plans or beams through anatomies larger than the predetermined voxel grid must be done in steps, obtaining several input volumes and accumulating the outputs along the beam depth.…”
Section: Discussionmentioning
confidence: 99%
“…For dose prediction in finer grid resolutions, iDoTA can be coupled to neural representation models capable of accurate super-resolution. 50 Regarding grid size, predicting dose distributions from treatment plans or beams through anatomies larger than the predetermined voxel grid must be done in steps, obtaining several input volumes and accumulating the outputs along the beam depth. Conversely, all doses can be predicted for the same fixed grid covering the part of the anatomy containing the structures of interests, which neglects the (usually) low doses near patient entrance.…”
Section: Limitationsmentioning
confidence: 99%
“…iDoTA is trained using a certain resolution and grid dimensions, which must be fixed for both training and inference. For dose prediction in finer grid resolutions, iDoTA can be coupled to neural representation models capable of accurate super-resolution [49]. Regarding grid size, predicting dose distributions from treatment plans or beams through anatomies larger than the predetermined voxel grid must be done in steps, obtaining several input volumes and accumulating the outputs along the beam depth.…”
Section: Discussionmentioning
confidence: 99%
“…Similar with previous work on NeRP learning for imaging and treatment planning, 23,24 a MLP network 20,21 was implemented. The network consists of eight fullyconnected layers.…”
Section: Network Structurementioning
confidence: 99%
“…Recent research has shown significant promise in using NeRP to accurately model traditional discrete representations that use pixel/voxel grids. This technique has been successfully applied to many tasks such as computed tomography (CT) and magnetic resonance image (MRI) reconstruction, 23 dosimetric plan representation, 24 generative modeling, 25 synthesizing high-resolution 3D shapes using coarse voxels, 26,27 compressing 2D images and videos 28 and neural rearrangement planning for unknown objects. 29 By learning the NeRP of the "golden" beam dataset, we assumed that the prior knowledge of the Linac beam data was embedded through network weights and can be used to assist inference of full beam dataset from sparse measurements, where the prior-embedded network was further trained to fit a subset of beam data measured and the complete set of beam data was predicted by querying the trained network.…”
Section: Introductionmentioning
confidence: 99%